2008
DOI: 10.1016/j.neuropsychologia.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the posterior parietal lobe involved in working memory retrieval?

Abstract: Neuroimaging evidence suggests that the parietal lobe has an important role in memory retrieval, yet neuropsychology is largely silent on this topic. Recently, we reported that unilateral parietal lobe damage impairs various forms of visual working memory when tested by old/new recognition. Here, we investigate whether parietal lobe working memory deficits are linked to problems at retrieval. We tested two patients with bilateral parietal lobe damage in a series of visual working memory tasks that probed recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 72 publications
2
40
0
Order By: Relevance
“…Diwadkar et al [42] found that PA and DLPFC were activated during kinesis in spatial working memory. Berryhill and Olson [43] found that the posterior part of bilateral BA7 played an important role in maintaining visual working memory, which acted as visual-space storage in the working memory model. In our study, the bilateral DLPFC and right precuneus of the Pre-SCH group were not as activated as those in the euthyroidism group, which might suggest that the miopragia of spatial working memory of SCH patients was related to the hypofunction of DLPFC - posterior part of PA network.…”
Section: Discussionmentioning
confidence: 99%
“…Diwadkar et al [42] found that PA and DLPFC were activated during kinesis in spatial working memory. Berryhill and Olson [43] found that the posterior part of bilateral BA7 played an important role in maintaining visual working memory, which acted as visual-space storage in the working memory model. In our study, the bilateral DLPFC and right precuneus of the Pre-SCH group were not as activated as those in the euthyroidism group, which might suggest that the miopragia of spatial working memory of SCH patients was related to the hypofunction of DLPFC - posterior part of PA network.…”
Section: Discussionmentioning
confidence: 99%
“…Next, four shapes (randomly selected without replacement from a set of ten) were presented (1000 ms). Stimuli were bilaterally symmetrical abstract shapes (7° × 7°) generated by a computer algorithm described previously (e.g., (Berryhill & Olson, 2008; Jiang, Olson, & Chun, 2000). Each shape reversed contrast (black, white) at one of four distinct temporal frequencies: 3 Hz, 5 Hz, 12 Hz, and 20 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…An additional benefit of a bilateral montage is that the current flow of tDCS is more restricted to the cortical regions of interest compared to unilateral montages (Vines et al, 2008), which is important because tDCS brings about network changes even in regions that are not stimulated (Keeser et al, 2011; Lang et al, 2005), suggesting that unilateral stimulation can modulate the contralateral hemisphere and lead to behavioral effects. Bilateral tDCS can therefore oppose such modulation and, in the case of the PPC, may be a better model for mnemonic contributions because changes to memory have been primarily noted in patients with bilateral lesions (Berryhill et al, 2007; Berryhill and Olson, 2008; Drowos et al, 2010; Simons et al, 2010). Thus, in our study we used bilateral montages, placing the anode over the left hemisphere and cathode over the right hemisphere, to determine the nature of the causal role of the PPC in item and source memory retrieval.…”
Section: Introductionmentioning
confidence: 99%